Penerapan Platform Digital untuk Meningkatkan Efektivitas Koordinasi dan Transparansi Informasi Pendamping Desa Bidang Pembangunan di Kecamatan Bantan - Tengku Musri Tengku Musri; Muhamad Nasir; Eva Kurniawaty Eva Kurniawaty; Ayu Rahmadhani Ayu Rahmadhani (P3M Politeknik Negeri Bengkalis, 2026)
In the current information era, the utilization of digital technology has become an essential requirement across various sectors, including government administration. Technological advancements are not only adopted by the private sector but also by government institutions to improve service quality and the effectiveness of information management. This community service activity aims to develop and implement a digital platform for village facilitators to support the execution of their duties in coordination, reporting, and monitoring village development activities. The developed platform is web-based, allowing online access for village facilitators, sub-district governments, and other related stakeholders. The system provides features for delivering development information, activity reporting, and structured and transparent documentation of progress. The implementation of this platform is expected to enhance the speed, efficiency, and accountability of coordination processes without relying on face-to-face meetings. The results indicate that the use of a digital platform improves the flow of information distribution and facilitates the monitoring of village development activities. However, to ensure data accuracy and report feasibility, continuous validation and verification mechanisms are still required.necessary.